Self-hurt behaviors among adolescents in Malaysia: a case study - Guan, Teik Ee; See, Ching Mey (2011)
World Health Organisation reported that self-hurt has been emerging as one of the problems contributing to the rise in the morbidity and mortality rates (World Health Organisation, 2001). Literature also shows that repetitive self-hurt increased the risk of completed suicide. Previous research suggeated that the number of young people who hurt themselves is growing significantly in the recent years. Thus, it is important to find out the status of self-hurt among the young people in Malaysia. The purpose of this study is to find out the types of self-hurt behaviour among adolescents in Malaysia using the Functional Assessment of Self-Mutilation Instrument (FASM) by Lloyd, E.E., Kelly, M.L., & Hope, T. (1997). The instrument was modified and translated to Bahasa Malaysia. The reliability of the types of self-hurt was tested. Ninety-six students aged 17 years took part in answering the modified FASM (Bahasa Malaysia version). An analysis of types of self-hurt behaviour was performed. The findings and implications are discussed.